Earthquake resilient coupling beams: a state-of-the-art review - GUAN Minsheng; LI Zhenying; DU Hongbiao (Shenzhen Daxue xuebao. Ligong ban)
Coupling beams are significant members to dissipate energy in shear wall structures among which the earthquake resilient coupling beam possesses such advantages as good capacity of energy dissipation, effectiveness of reducing the inter-story drift and the damage to the main structure, as well as the replaceable characteristic after earthquakes. Thus it has become one of the research hotspots of earthquake resilient structures. The research advances of the resilient coupling beam are valuated based on how it works from three main aspects: decrease in the cross section of coupling beam, addition of energy dissipation device and improvement in the self-centering ability of coupling beam. Moreover, the characteristics of various resilient coupling beams are put forward, namely, coupling beams with decrease in the cross section, relatively unsophisticated in structure, are thus accessible for construction, whereas their residual deformation is rather augmented after the earthquake; while those with additional energy dissipation device retain good capacity of dissipating energy, the damage to other components is generated for the fairly large deformation of the damper; self-centering coupling beams show superior performance in mitigating the residual deformation effectively, but their beam elongation effect is more significant. Finally, the design scheme related to a novel type of self-centering double coupling beam is proposed in which the structures and advantages of the proposed beam are introduced. This review provides a reference for the seismic design of the coupling beam.